Marine-Derived Compounds Combined with Nanoparticles: A Focus on the Biomedical and Pharmaceutical Sector - Laura M. Teixeira; Catarina P. Reis; Rita Pacheco (Marine Drugs)
The ocean is an extraordinary natural source of a wide range of bioactive compounds. These compounds, including proteins, phenolics, polysaccharides, pigments, vitamins, and fatty acids, possess unique biological properties that are increasingly being explored in the field of nanotechnology across diverse sectors. Among marine-derived nanoparticles, promising applications have emerged in the biomedical and pharmaceutical fields, particularly metallic nanoparticles and polysaccharide-based drug delivery systems. This review provides a unique perspective on the integration of two research areas: the exploration of marine bioresources as bioactive compounds sources with nanotechnological methodologies to develop sustainable, safe, stable and functional marine-derived NPs. It highlights recent advancements in the green synthesis of MNPs and the formulation of drug delivery systems using marine polysaccharides. This review also describes the recent trends over the past ten years and discusses the major challenges and limitations associated with these approaches, including variability in biological sources, batch-to-batch inconsistency, mechanistic uncertainties, and difficulties in reproducibility and scalability. Furthermore, it emphasizes the need for standardized protocols and the integration of life cycle assessments (LCA) to evaluate environmental and economic viability for effective translating marine-derives nanoparticles from research to clinical applications.